PDIA3 rs2788: An Independent Risk Factor for Hypertension and Its Interaction With Antihypertensive Medications - Hongtao Lan; Yingbin Xi; Baoxu Kang; Zhoujie Tong; Jie Peng; Wei Zhang; Ming Zhong; Huiping Gong; Zhihao Wang (The Journal of Clinical Hypertension)
ABSTRACT Hypertension is a multifactorial condition influenced by both genetic and environmental factors. Protein disulfide isomerase family A member 3 (PDIA3) is a key endoplasmic reticulum protein which may contribute to increased blood pressure. However, the relationship between PDIA3 polymorphisms and hypertension remain unclear. This study aims to explore the relationship between PDIA3 polymorphisms and hypertension. First, Mendelian randomization (MR) analyses were performed to assess the causal link between PDIA3 and hypertension. Second, key gene polymorphism on PDIA3 was identified using online databases and analyzed with Haploview software. Third, multivariate‐adjusted logistic regression analyses were employed to evaluate the associations between PDIA3 rs2788 and hypertension. Finally, stratified analyses were conducted to further assess interactions between PDIA3 rs2788 and antihypertensive medications. MR analyses indicated a causal relationship between PDIA3 and hypertension. The rs2788 gene polymorphism locus on PDIA3 was identified using online databases and Haploview software. Multivariable‐adjusted logistic regression analyses revealed that PDIA3 rs2788 was an independent risk for hypertension (OR: 4.603, 95% CI: 2.946–7.194; p < 0.001). Significant interactions were identified between PDIA3 and antihypertensive medications, particularly ACEI/ARB treatments (p = 0.013 for interaction). Similar findings were observed regarding the causal relationship between antihypertensive treatments and hypertension. PDIA3, particularly its rs2788 polymorphisms, may represent a novel biomarker for hypertension. These findings may contribute to the development of targeted screening strategies and personalized treatment approaches for hypertension management.